If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x/2-4=2x-1
We move all terms to the left:
x/2-4-(2x-1)=0
We get rid of parentheses
x/2-2x+1-4=0
We multiply all the terms by the denominator
x-2x*2+1*2-4*2=0
We add all the numbers together, and all the variables
x-2x*2-6=0
Wy multiply elements
x-4x-6=0
We add all the numbers together, and all the variables
-3x-6=0
We move all terms containing x to the left, all other terms to the right
-3x=6
x=6/-3
x=-2
| 5y+6=4y+8 | | (4x+6x)+-20=80 | | 11/1/2=a | | -7x-17=32 | | -8(x+9)=64 | | 5/8h=11/2=5 | | -6(x-8)=36 | | 4(n=1)+2n+3=55 | | 9y-35+125=180 | | 7x+8=15-(16+24) | | 17=4x+5x | | k-2.6=2.1736 | | 3x•4=x+11 | | 12=11y-9y | | (16+x)^2+x^2=729 | | 5w-w=28 | | 2x^2+32x-473=0 | | n/5-12=6 | | 4-9g=-23 | | 9v-5v=24 | | 36+3w=-36 | | 16+x+10=8x-16 | | 67+10x+8+11x=180 | | 46+2x=92 | | 295=v=+24 | | 5d+20=-30 | | 2x+5.5=22 | | 9c-40=50 | | -56+c=7 | | p+9.3=0.7 | | 108-y=267 | | -31.5=-6b |